PERAN MANAJEMEN DAKWAH DALAM KEGIATAN KEAGAMAAN PADA SEKSI BIMAS ISLAM DI KANTOR KEMENTRIAN AGAMA KABUPATEN GOWA - HASARUDDIN, HASARUDDIN; WAHYUNI, SRI (Jurnal Dakwah Tabligh, 2019)
The main problem of this research is the role of da’wah management in religious activities in the Islamic Community section in the office of the Ministry of Religion, Gowa Regency. Then presents 2 sub-problems, namely religious activities carried out in the Islamic Community section in the office of the Ministry of Religion, Gowa Regency and the efforts of the Islamic Bimas section in organizing religious activities in the office of the Ministry of Religion of Gowa Regency. The results of this study indicate that religious activities carried out in the Islamic Community Guidance Section in the Office of the Ministry of Religion of Gowa Regency are: 1) Counseling of Instructors and Executives, 2) Guidance of Mosque 3) Development of Sakinah Families 4) Development of Endowments Zakat. In arranging religious activities in the Islamic Community Guidance Section has implemented Da’wah management functions, among others: Takhthit (missionary planning), Tanzhim (organizing), Tawjih (movement / implementation), Riqabah (control), and evaluation.